2009
DOI: 10.1111/j.1439-0531.2009.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Examination of the Corpora Lutea from Pregnant Bitches Treated with Different Abortifacient Regimes

Abstract: Different abortifacient regimes in dogs were analysed for their effect on the pregnancy corpora lutea (CL), namely, prostaglandin F2a analogue cloprostenol (CLO) combined with dopamine agonist cabergoline (CAB), or progesterone (P4) receptor antagonist aglepristone (AGL). Ovaries were collected after 6-10 days of treatment during first trimester. The CL of the control-group showed strong expression of relaxin (RLX), its receptor RXFP1 and enzymes of steroid biosynthesis (HSD) with high peripheral P4-levels. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It is likely that the majority of changes seen in pregnancy are driven by the hormones estrogen and progesterone ( 56 58 ). Increasing concentrations of both hormones positively correlate with increasing gestation and successful pregnancy ( 56 , 59 , 60 ). Estrogen has been shown to promote immune tolerance by inhibiting CD4 T cell expansion and promoting apoptosis, increasing Treg proportions, and promoting tolerant DC expressing inhibitory markers ( 61 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the majority of changes seen in pregnancy are driven by the hormones estrogen and progesterone ( 56 58 ). Increasing concentrations of both hormones positively correlate with increasing gestation and successful pregnancy ( 56 , 59 , 60 ). Estrogen has been shown to promote immune tolerance by inhibiting CD4 T cell expansion and promoting apoptosis, increasing Treg proportions, and promoting tolerant DC expressing inhibitory markers ( 61 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, this is not evident in humans, and thus it is expected that a different mechanism of change in physiological P4 action is required to mediate human labor (15, 16). This has been supported by both animal and human studies that have used abortifacient regimens, either by (i) inducing a decline in systemic P4 levels, (ii) corpus luteum lysis or oophorectomy, or (iii) directly antagonizing the effects of P4 by the administration of an anti-progestin such as mifepristone (RU486) (1722). It has been strongly suggested that the ability of RU486 to promote abortions and labor demonstrates such uterine processes are driven by “functional P4 withdrawal” in humans, which is mediated by altering the expression levels of P4 receptor (PR) isoforms and PR gene polymorphisms in reproductive tissues (2325).…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, high P4 concentrations in bitches during AGL treatment can be considered normal. However, whereas some authors report that a significant increase in P4 concentrations occurs after the first AGL treatment [ 24 , 28 , 71 , 72 ], others report an insignificant change in P4 concentrations after AGL treatment [ 43 , 69 , 73 ]. In this study, the change in the P4 concentrations of the bitches treated with AGL was insignificant, and no increase occurred after the first AGL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that parturition and PT begin with prepartum luteolysis, which is characterized by a decrease in peripheral P4 concentrations and the downregulation of StAR and 3β-HSD expressions in luteal cells in response to an increase in PGF 2 α levels [ 13 , 74 ]. On the other hand, the decrease in P4 concentrations that triggers the mentioned regulatory pathway does not apply to AGL-induced parturition/PT [ 24 , 28 , 71 , 72 ] because AGL causes incomplete luteolysis [ 73 ]. Kowalewski et al [ 75 ] showed that blocking PGRs by AGL leads to the activation of the prostaglandin system in the luteal and placental tissues, with a similar occurrence during normal prepartal luteolysis.…”
Section: Discussionmentioning
confidence: 99%